Tinjauan Yuridis Terhadap Upacara Ngaben (Pitra Yadnya) di Masa Pandemi Covid-19 dan Pelaksanaan Pemberlakuan Pembatasan Kegiatan Masyarakat (PPKM) di Provinsi Bali - Ni Kadek Madya Yani; I Nyoman Gede Sugiartha; Diah Gayatri Sudibya (Warmadewa Press, 2022)
PPKM has been the policy of the Government of Indonesia to combat the Covid-19 pandemic since the beginning of 2021. PPKM has a great influence in the Ngaben ceremony. Ngaben is a ceremony to purify spirits and smelting corpses by burning the bodies of people who have died. This study aims to examine the legal regulation of PPKM in relation to the Ngaben ceremony in Bali and to uncover legal sanctions against people who violate PPKM during the Ngaben ceremony in Bali. This research is designed with normative legal research with legislation approach and case approach. Sources of data used are primary and secondary data obtained through library research techniques. After the data is collected, it is then processed and analyzed descriptively qualitatively. The results of the study show that there are legal arrangements and sanctions for PPKM violators in relation to the Ngaben ceremony, namely the Instruction of the Minister of Home Affairs Number 35 of 2021 and the Governor's Circular Letter Number 12 of 2021.